Melanoma cell adhesion molecule-positive CD8 T lymphocytes mediate central nervous system inflammation - Larochelle, Catherine; Lécuyer, Marc-André; Alvarez, Jorge Ivan; Charabati, Marc; Saint-Laurent, Olivia; Ghannam, Soufiane; Kebir, Hania; Flanagan, Ken; Yednock, Ted; Duquette, Pierre; Arbour, Nathalie; Prat, Alexandre (Annals of neurology, 2015)
Objective Although Tc17 lymphocytes are enriched in the central nervous system (CNS) of multiple sclerosis (MS) subjects and of experimental autoimmune encephalomyelitis (EAE) animals, limited information is available about their recruitment into the CNS and their role in neuroinflammation. Identification of adhesion molecules used by autoaggressive CD8+ T lymphocytes to enter the CNS would allow further characterization of this pathogenic subset and could provide new therapeutic targets in MS. We propose that melanoma cell adhesion molecule (MCAM) is a surface marker and adhesion molecule used by pathogenic CD8+ T lymphocytes to access the CNS. Methods Frequency, phenotype, and function of MCAM+CD8+ T lymphocytes was characterized using a combination of ex vivo, in vitro, in situ, and in vivo approaches in humans and mice, including healthy controls, MS subjects, and EAE animals. Results Herein, we report that MCAM is expressed by human effector CD8+ T lymphocytes and it is strikingly upregulated during MS relapses. We further demonstrate that MCAM+CD8+ T lymphocytes express more interleukin 17, interferon γ, granulocyte‐macrophage colony–stimulating factor, and tumor necrosis factor than MCAM− lymphocytes, and exhibit an enhanced killing capacity toward oligodendrocytes. MCAM blockade restricts the transmigration of CD8+ T lymphocytes across human blood–brain barrier endothelial cells in vitro, and blocking or depleting MCAM in vivo reduces chronic neurological deficits in active, transfer, and spontaneous progressive EAE models. Interpretation Our data demonstrate that MCAM identifies encephalitogenic CD8+ T lymphocytes, suggesting that MCAM could represent a biomarker of MS disease activity and a valid target for the treatment of neuroinflammatory conditions. Ann Neurol 2015;78:39–53